Kekerasan Seksual di Penjara Syariat Melalui @JurnalisKomik - Deviana Fauziyyah Nabilah; Askurifa’I Baksin (Jurnal Riset Jurnalistik dan Media Digital, 2021)
Abstract. Today there are various new genres in the world of journalism, one of which is comic journalists who marry journalistic writing with comic illustrations. Like the report titled "Sexual Violence in Sharia Prison" that occurred in Langsa Aceh, through its comic @ journaliscomics conveys messages or signs contained in the picture, this indicates that a comic illustration contains many signs that have meaning, purpose, and purpose.Therefore the purpose of this research is to find out (1) the meaning of the denotation of the news content “Sexual Violence in Sharia Prison” which is packaged through comic journalism in Instagram @jurnaliskomik social media (2) the meaning of the connotation of news content “Sexual Violence in Sharia Prison” which is packaged through comic journalism on social media Instagram @ jurnaliskomik (3) knowing the myth in the news content “Sexual Violence in Sharia Prison” which is packaged through comic journalism on Instagram @jurnaliskomik social media.The study uses qualitative research methods with Roland Barthes's semiotic analysis approach through observation, interview and literature study data collection techniques. The object of the research is the news content in the form of comic panels in Instagram @jurnaliskomik which is manifested a “sexual Violence in Sharia Prison” The supporting informants to be a comparison of this research are comic artists from the JurnalisKomik. The results of this study are as follows: (1) The meaning of denotation in the news “Sexual Violence imprisoned by Shari'a” as quite striking contrast coloring and facial features in comic characters show various expressions according to the context that is happening, so it is easily digested by its readers (2) the meaning of the connotation in the news“Sexual Violence in Sharia Prison” shows the existence of sad feelings because the incident occurred in Langsa City, Aceh which has an image of a region with people who are religious and run Islamic law (3) Myth in the news“Sexual Violence in Sharia Prison” illustrates women's feelings are weak according to Eastern culture and there is no power and effort to defend themselves. Abstrak. Dewasa ini terdapat berbagai genre baru di dunia jurnalistik, salah satunya jurnalis komik dengan mengawinkan penulisan jurnalistik dengan ilustrasi komik. Seperti pemberitaan berjudul “Kekerasan Seksual di Penjara Syariat” yang terjadi di Langsa Aceh, Melalui komiknya @jurnaliskomik menyampaikan pesan-pesan atau tanda-tanda yang terkandung di dalam gambarnya, hal tersebut menandakan bahwa sebuah ilustrasi komik mengandung banyak tanda yang memiliki makna, maksud, dan tujuan. Maka dari itu tujuan Penelitian ini adalah untuk mengetahui (1) makna denotasi konten berita “Kekerasan Seksual di Penjara Syariat” yang dikemas melalui jurnalisme komik dalam media sosial Instagram @jurnaliskomik (2) makna konotasi konten berita “Kekerasan Seksual di Penjara Syariat” yang dikemas melalui jurnalisme komik dalam media sosial Instagram @jurnaliskomik (3) mengetahui mitos dalam konten berita “Kekerasan Seksual di Penjara Syariat” yang dikemas melalui jurnalisme komik dalam media sosial Instagram @jurnaliskomik. Penelitian menggunakan metode penelitian kualitatif dengan pendekatan analisis semiotic Roland Barthes melalui teknik pengumpulan data observasi, wawancara, studi pustaka. Untuk objek penelitiannya adalah konten berita berupa panel-panel komik dalam Instagram @jurnaliskomik yang berujudul “Kekerasan Seksual Di Penjara Syariat” Adapun narasumber pendukung untuk menjadi perbandingan penelitian ini yaitu komikus dari JurnalisKomik. Hasil dari penelitian ini sebagai berikut: (1) Makna denotasi dalam berita “Kekerasan Seksual dipenjara Syariat” memiliki kontras pewarnaan cukup mencolok dan detail raut wajah dalam karakter komik menunjukkan ekspresi yang beragam sesuai dengan konteks yang sedang terjadi, sehingga mudah dicerna oleh pembacanya (2) makna konotasi dalam berita “Kekerasan Seksual dipenjara Syariat” menujukkan adanya perasaan miris karena kejadian tersebut terjadi di Kota Langsa, Aceh yang memiliki image wilayah dengan penduduk yang taat beragama dan menjalankan syariat Islam (3) Mitos dalam berita “Kekerasan Seksual dipenjara Syariat” menggambarkan perasaan wanita yang lemah menurut kebudayaan Timur dan tiada daya sertaupaya untuk membela diri.